Effects of distance to market, season, and family wealth on pastoral dairy marketing in Ethiopia - Holden, S.J.; Coppock, D. Layne (1992)
Presents results of a survey designed to determine the effects of distance to market, family wealth, and season on the quantity of dairy products sold per person and per lactating animal. Quantifies the contribution of dairy marketing to the household economy on an annual and seasonal basis and assesses the role of dairy marketing in terms of pastoral food security. Includes data on family size and holdings of lactating livestock for pastoral households of varied wealth.